Highly Oxidation‐Resistant Electrolyte for 4.7 V Sodium Metal Batteries Enabled by Anion/Cation Solvation Engineering. (29th November 2022) - Wu, Daxiong; Zhu, Chunlei; Wu, Mingguang; Wang, Huaping; Huang, Junda; Tang, Dongliang; Ma, Jianmin
Abstract: Sodium metal batteries (SMBs) are considered as promising battery system due to abundant Na sources. However, poor compatibility between electrolyte and cathode severely impedes its development. Herein, we proposed an anion/cation solvation strategy for realizing 4.7 V resistant SMBs electrolyte with NaClO4 and trimethoxy(pentafluorophenyl)silane (TPFS) as dual additives (DA). The ClO4 − can rapidly transfer to the cathode surface and strongly coordinate with Na + to form stable polymer‐like chains with solvents. Meanwhile, TPFS can preferentially enter into the PF6 − anion solvation sheath for reducing PF6 ‐solvent interaction and effectively scavenge adverse electrolyte species for protecting electrode electrolyte interphases. Thus, such electrolyte elevates the oxidative stability of carbonate electrolytes from 3.77 to 4.75 V, and enables Na||Na3 V2 (PO4 )2 O2 F (NVPF) battery with a capacity retention of 93 % and an average Coulombic efficiency (CE) of 99.6 % after 500 cycles at 4.7 V. Abstract : A 4.7 V oxidation‐resistant electrolyte with self‐purifying ability is successfully designed by anion/cation solvation strategy with NaClO4 and TPFS as dual additives. The Na||NVPF battery with such electrolyte could exhibit superior electrochemical performance.